2010
DOI: 10.1007/978-3-642-15509-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Research on Quality of Transaction Standards: The Maturity of a Research Topic

Abstract: Abstract. This paper contains the results of a systematic literature review executed to determine the coverage of transaction standards in top information systems (IS) and management journals. Specifically, it aims to identify a research gap with respect to this topic. The top 25 journals are thoroughly searched and the selected publications are classified in order to make grounded statements. A moderate amount of literature found specifically aims at transaction standards. Hardly any research is found on qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Recent study have identified a research gap on quality of transactional standards [11]. A systematic literature study was conducted that covered the top 25 journals of information systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recent study have identified a research gap on quality of transactional standards [11]. A systematic literature study was conducted that covered the top 25 journals of information systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the ''Solution design'' is relatively well supported by existing literature, hardly any contribution can be found in the scientific body of knowledge regarding the ''Conceptual solution'' and the ''Technical solution''. Many studies on standardization are focused on the development of standards (Folmer et al 2010). This is closely related to the management of standards, involving standards development organizations.…”
Section: Sub-categories and Concepts Of The Category ''Content''mentioning
confidence: 99%
“…Existing standard research suggest that standard adoption is dependant on the aspects that that standard have [1], however most research describe technical standards (like the USB and IPv6 standards). Research describing business transaction standards is scarce [4]. Furthermore because of political, organizational, and economic complexities [5] business transaction standard development differ from technical standards and thus indicates that the aspects form technical standards are not necessarily the same as business transaction standards.…”
mentioning
confidence: 99%